2020
DOI: 10.1038/s41598-020-61041-y
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II represses Npr1 expression and receptor function by recruitment of transcription factors CREB and HSF-4a and activation of HDACs

Abstract: The two vasoactive hormones, angiotensin II (ANG II; vasoconstrictive) and atrial natriuretic peptide (ANP; vasodilatory) antagonize the biological actions of each other. ANP acting through natriuretic peptide receptor-A (NPRA) lowers blood pressure and blood volume. We tested hypothesis that ANG ii plays critical roles in the transcriptional repression of Npr1 (encoding NPRA) and receptor function. ANG II significantly decreased NPRA mRNA and protein levels and cGMP accumulation in cultured mesangial cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Currently, four HDACIs have been approved by the U.S. Food and Drug Administration (FDA) for clinical use in hematologic tumors ( Qin et al, 2017 ), while HADCIs in fibrotic diseases are still being examined in preclinical studies. For example, trichostatin A, a pan HDACI, has shown benefits in multiple fibrosis models ( Lan et al, 2015 ; Wu et al, 2017 ; Yoon et al, 2019 ), and SK-7041, a class I HDAC-selective inhibitor, ameliorates fibrotic conditions in cardiac and renal mouse models ( Arise et al, 2020 ; Martinez-Moreno et al, 2020 ). Unlike other diseases in which one therapeutic target will be sufficient, fibrotic diseases sometimes require combined epigenetic therapy.…”
Section: Current Clinical Trials In Fibrotic Diseasesmentioning
confidence: 99%
“…Currently, four HDACIs have been approved by the U.S. Food and Drug Administration (FDA) for clinical use in hematologic tumors ( Qin et al, 2017 ), while HADCIs in fibrotic diseases are still being examined in preclinical studies. For example, trichostatin A, a pan HDACI, has shown benefits in multiple fibrosis models ( Lan et al, 2015 ; Wu et al, 2017 ; Yoon et al, 2019 ), and SK-7041, a class I HDAC-selective inhibitor, ameliorates fibrotic conditions in cardiac and renal mouse models ( Arise et al, 2020 ; Martinez-Moreno et al, 2020 ). Unlike other diseases in which one therapeutic target will be sufficient, fibrotic diseases sometimes require combined epigenetic therapy.…”
Section: Current Clinical Trials In Fibrotic Diseasesmentioning
confidence: 99%
“…Therefore, the study suggests that Ang-II-mediated Npr1 transcription and receptor function inhibition may provide new molecular targets and an important theoretical basis for the treatment and prevention of hypertension. 117 In conclusion, these studies indicate that histone acetylation is closely related to cardiovascular diseases mechanism.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 65%
“… 115 Downregulation of SIRT3 expression and SIRT3 redox inactivation result in superoxide dismutase 2 (SOD2) inactivation, which promotes the occurrence of hypertension. 116 In addition, Arise et al 117 found that angiotensin II(Ang II) enhanced the activity of class I HDAC1/2, reduced histone acetylation of H3K9/14ac and H4K8ac, further inhibited Npr1 (encoding natriuretic peptide receptor-A) transcription, and decreased natriuretic peptide receptor-A protein and cGMP levels, thereby diminishing renal and vascular reactivity and attenuating atrial natriuretic peptide-mediated aortic ring relaxation. Therefore, the study suggests that Ang-II-mediated Npr1 transcription and receptor function inhibition may provide new molecular targets and an important theoretical basis for the treatment and prevention of hypertension.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 99%
“…Those studies indicated that phosphorylation at serine and threonine sites induces the desensitization of GC-coupled receptors. In fact, the activation of GC-A/NPRA could also be attenuated by agents such as certain growth factor, including epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) and pressure hormones, such as endothelin, vasopressin, and ANG II, which decrease the responsiveness of GC-A/NPRA ( Haneda et al, 1991 ; Yasunari et al, 1992 ; Potter and Garbers, 1994 ; Kumar et al, 1997 ; Pandey et al, 2000 ; Sharma et al, 2002 ; Garg and Pandey, 2003 ; Tripathi and Pandey, 2012 ; Alicic et al, 2018 ; Arise et al, 2020 ). The agonist-dependent activation of PKC by phorbol ester decreased GC catalytic activity of NPRA ( Haneda et al, 1991 ; Yasunari et al, 1992 ; Potter and Garbers, 1994 ; Kumar et al, 1997 ; Pandey, 2005 ; Kumar et al, 2017 ).…”
Section: Signal Transduction Mechanisms and Intracellular Signaling O...mentioning
confidence: 99%